Synthesis and Characterization of Tissue Plasminogen Activator—Functionalized Superparamagnetic Iron Oxide Nanoparticles for Targeted Fibrin Clot Dissolution - Heid, Susanne (Int J Mol Sci, 2017)
Superparamagnetic iron oxide nanoparticles (SPIONs) have attracted great attention in many biomedical fields and are used in preclinical/experimental drug delivery, hyperthermia and medical imaging. In this study, biocompatible magnetite drug carriers, stabilized by a dextran shell, were developed to carry tissue plasminogen activator (tPA) for targeted thrombolysis under an external magnetic field. Different concentrations of active tPA were immobilized on carboxylated nanoparticles through carbodiimide-mediated amide bond formation. Evidence for successful functionalization of SPIONs with carboxyl groups was shown by Fourier transform infrared spectroscopy. Surface properties after tPA immobilization were altered as demonstrated by dynamic light scattering and ζ potential measurements. The enzyme activity of SPION-bound tPA was determined by digestion of fibrin-containing agarose gels and corresponded to about 74% of free tPA activity. Particles were stored for three weeks before a slight decrease in activity was observed. tPA-loaded SPIONs were navigated into thrombus-mimicking gels by external magnets, proving effective drug targeting without losing the protein. Furthermore, all synthesized types of nanoparticles were well tolerated in cell culture experiments with human umbilical vein endothelial cells, indicating their potential utility for future therapeutic applications in thromboembolic diseases.